2014
DOI: 10.3109/0886022x.2014.947516
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and chronic kidney disease: an enigma yet to be solved

Abstract: The role of uric acid (UA) on the pathogenesis and progression of chronic kidney disease (CKD) remains controversial. Experimental and clinical studies indicate that UA is associated with several risk factors of CKD including diabetes, hypertension, oxidative stress, and inflammation and hyperuricemia could be considered as a common dominator linking CKD and cardiovascular disease. Notably, the impact of serum UA levels on the survival of CKD, dialysis patients, and renal transplant recipients is also a matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 145 publications
(170 reference statements)
1
51
0
1
Order By: Relevance
“…On the other hand, epidemiologic evidence and experimental models also have shown that hyperuricemia may impose detrimental effects as a prooxidant [8992]. UA is often associated with other risk factors of CKD, including diabetes, hypertension, and inflammation [93], which makes it difficult to dissect the role of UA itself in the progression of CKD. However, a recent study showed an association between hyperuricemia and renal damage independently of hypertension and intrarenal renin-angiotensin system (RAS) activation [94].…”
Section: Nadph Oxidase and Hyperuricemia-related Kidney Diseasementioning
confidence: 99%
“…On the other hand, epidemiologic evidence and experimental models also have shown that hyperuricemia may impose detrimental effects as a prooxidant [8992]. UA is often associated with other risk factors of CKD, including diabetes, hypertension, and inflammation [93], which makes it difficult to dissect the role of UA itself in the progression of CKD. However, a recent study showed an association between hyperuricemia and renal damage independently of hypertension and intrarenal renin-angiotensin system (RAS) activation [94].…”
Section: Nadph Oxidase and Hyperuricemia-related Kidney Diseasementioning
confidence: 99%
“…This question was examined with a correlational, rather than temporally restricted design, because of circularity in associations of gout and kidney dysfunction as well as the duration of available claims data. Although CKD can lead to hyperuricemia (due to impaired uric acid excretion), more recently, it has been suggested that uric acid may, itself, contribute to the development and progression of CKD (4-7). Notably, a recent pilot study found that higher pre-donation serum uric acid was associated with larger GFR reductions at 6 months post-donation among women (15).…”
Section: Discussionmentioning
confidence: 99%
“…To complicate this association, elevated serum uric acid levels have been implicated as a risk factor for the development and progression of CKD (4-7). A recent systematic review and meta-analysis found that hyperuricemia was an independent predictor of newly diagnosed CKD in the non-CKD population (5).…”
Section: Introductionmentioning
confidence: 99%
“…The predictive value of UA in regard to the progression of CKD is matter of controversy [5]- [11]. Although a causal role of HU in CKD has not been estab- [35].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the serum uric acid (UA) on renal prognosis of CKD patients has recently been attracting attention [3], and our group has reported finding that the serum UA value can serve as a predictor of progression of kidney disease in biopsy-proven nephrosclerosis patients [4]. However, because the serum UA elevation due to the decreased renal UA clearance in CKD patients makes it difficult to assess the role of UA in the progression of CKD, the predictive value of UA in regard to the progression of CKD remains a matter of controversy [5]- [11].…”
Section: Introductionmentioning
confidence: 99%